(untitled) (Journal of Human Sciences, 2025)
This study examines the role of the Public Prosecution in civil litigation, focusing on its powers of intervention, appeal, and protection of legality under both Libyan and Egyptian law. In addition to its original jurisdiction in the criminal field, the Public Prosecution undertakes civil functions to safeguard the public interest and public order, whether through mandatory or discretionary intervention in lawsuits. Its involvement in matters of personal status for foreigners, bankruptcy, and nationality disputes represents key aspects of this role. Failure to intervene when legally required results in the nullity of the judgment, while discretionary intervention remains subject to its own assessment without affecting the validity of the ruling. The Public Prosecution also holds the right to appeal civil judgments that violate public order and may file cassation appeals for the benefit of the law, thus reinforcing the principles of judicial legality. The research adopts an analytical and comparative methodology, analyzing relevant legal texts and judicial rulings from Libya and Egypt, aiming to highlight similarities and differences and to propose recommendations that enhance the effectiveness of the Public Prosecution’s role in civil matters.